Islamic Spirituality and Fear of Missing Out (FOMO): Revisiting ‘Uzlah in the Thought of Sheikh Nawawi al-Bantani - Ihsan, Nur Hadi; Karomi, Kholid; Zhoofiroh, Zalfaa' 'Afaaf; Mubarok, Deden Ruhiat (KALAM, 2025)
The rapid expansion of digital technology and social media has intensified the phenomenon of Fear of Missing Out (FOMO), a psychological condition characterized by anxiety arising from the perception of being excluded from rewarding social experiences. While existing studies have primarily examined FOMO from psychological and technological perspectives, limited attention has been given to the potential contribution of Islamic spiritual traditions in addressing this contemporary challenge. This study revisits the concept of ‘uzlah in the thought of Sheikh Nawawi al-Bantani and explores its relevance within the framework of Islamic spirituality in responding to the problem of FOMO in the digital era. Employing a qualitative library research approach, the study analyzes Nawawi al-Bantani’s writings and related classical and contemporary literature using content analysis. The findings indicate that ‘uzlah, understood as a conscious and temporary withdrawal from harmful social influences, functions as a spiritual discipline that strengthens worship, promotes self-reflection (tafakkur), cultivates emotional independence, and regulates social interaction. These elements contribute to reducing excessive social comparison and psychological pressure associated with hyper-connectivity in digital environments. The study argues that ‘uzlah should not merely be interpreted as physical isolation but as a form of ethical and spiritual regulation of social engagement. Consequently, the concept provides a meaningful framework within Islamic spirituality for addressing contemporary psychological challenges related to social media and digital life.